POSDAYA, MOMENTUM KEBANGKITAN EKONOMI UMAT - Luluk Indarinul Mufidah (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2017)
Indonesian population growth shows the rapid development, it’s shown by the results of the projection that for twenty-five next years, increasing from 205.100.000 in 2000 into 273.200.000 in 2025 (URwww.datastatistik-indonesia.com). It will cause a lot of issues, such as unemployment, increasing levels of poverty, public health, namely the spread of infectious disease, malnutrition children, etc. this condition requires the presence of efforts at community empowerment through POSDAYA (Pos Pemberdayaan Keluarga). The establishment of quality family is not only the responsibility of government alone, but also required the active participation of the community, so it is needed a good cooperation among the community and government to create an independent community. POSDAYA is the one of excellent breakthrough in creating independent community.